Specificity of the J-protein Sis1 in the propagation of 3 yeast prions - Higurashi, Takashi (National Academy of Sciences, 2008)
Yeast prions, such as [PSI(+)], [RNQ(+)], and [URE3], are heritable elements formed by proteins capable of acquiring self-perpetuating conformations. Their propagation is dependent on fragmentation of the amyloid protein complexes formed to generate the additional seeds necessary for conversion of nascent soluble protein to the prion conformation. We report that, in addition to its known role in [RNQ(+)] propagation, Sis1, a J-protein cochaperone of Hsp70 Ssa, is also specifically required for propagation of [PSI(+)] and [URE3]. Whereas both [RNQ(+)] and [URE3] are cured rapidly upon SIS1 repression, [PSI(+)] loss is markedly slower. This disparity cannot be explained simply by differences in seed number, as [RNQ(+)] and [PSI(+)] are lost with similar kinetics upon inhibition of Hsp104, a remodeling protein required for propagation of all yeast prions. Rather, in the case of [PSI(+)], our results are consistent with the partial impairment, rather than the complete abolition, of fragmentation of prion complexes upon Sis1 depletion. We suggest that a common set of molecular chaperones, the J-protein Sis1, the Hsp70 Ssa, and the AAA+ ATPase Hsp104, act sequentially in the fragmentation of all yeast prions, but that the threshold of Sis1 activity required for each prion varies.